Quantum chemistry - Levine, Ira N. (Prentice Hall, 2000)
Providing an introduction to quantum chemistry, this book covers quantum mechanics, atomic structure, and molecular electronic structure. It demonstrates the usefulness and limitations of quantum-mechanical methods for the calculation of molecular properties. It is useful for beginning graduate and advanced undergraduate courses in this field.